Transmission line EMTP models influence on time-domain fault location and protection functions during performance assessment tests - Ribeiro, Luiza Mendonça Aviani (2021)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2021.